Puberty age and marriage goals: Analysis of Tafsir Al Wajiz and Tafsir Karimir Rahman - Aulia, Muhammad Fadli Rahman; Taufiq, Wildan; Mokhtar, Ahmad Baha’ Bin (UIN Sunan Gunung Djati Bandung, 2025)
This study analyzes the concept of maturity and its relation to marriage goals through Tafsir Al-Wajiz by Wahbah az-Zuhaili and Tafsir Karimir-Rahman by Abdurrahman as-Sa‘di, focusing on key Quranic verses. Using thematic library research and Fazlur Rahman’s Double Movement theory, it finds Wahbah emphasizes biological and intellectual maturity tied to financial readiness, while As-Sa‘di highlights spiritual and moral maturity for building a strong Islamic family. The study concludes that maturity for marriage in Islam includes biological, psychological, social, and economic factors, informing Islamic legal policies on ideal marriage age based on maqāṣid asy-syarī‘ah principles.